2011
DOI: 10.1016/j.pec.2010.05.015
|View full text |Cite
|
Sign up to set email alerts
|

“I Wouldn’t Be this Firm if I Didn’t Care”: Preventive clinical counseling for reproductive health

Abstract: Objective-This qualitative study of the health care clinicians serving women at heightened risk of sexually transmitted infections and unintended pregnancy was undertaken to explore concepts underlying reproductive health counseling messages in clinical encounters.Methods-In-depth interviews were conducted with 31 clinicians, including physicians and advanced practice clinicians serving primarily low-income patients in high-risk communities throughout the U.S.Results-Most of the clinicians describe their influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
2
12
0
5
Order By: Relevance
“…Consistent with the findings of Henderson et al, 23 the doctors recognised some tension between the shared approach—informing patients of options and allowing autonomous decision making—and the reality of clinical consultations which sometimes involved more directive counselling. Our findings suggest doctors in part encourage methods according to their own preferences and their understanding of the latest evidence in the field, and this can sometimes merge back into a paternalistic rather than a shared model of care.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with the findings of Henderson et al, 23 the doctors recognised some tension between the shared approach—informing patients of options and allowing autonomous decision making—and the reality of clinical consultations which sometimes involved more directive counselling. Our findings suggest doctors in part encourage methods according to their own preferences and their understanding of the latest evidence in the field, and this can sometimes merge back into a paternalistic rather than a shared model of care.…”
Section: Discussionsupporting
confidence: 61%
“…One study of clinicians serving high-risk communities throughout the United States found that many reported having an influence on patients’ decisions about contraception, including through the use of scare tactics and by drawing on authority derived from their professional expertise. 40 In contrast, a similar study, also using qualitative methods, of providers serving African American adolescents in community health centers in Chicago found that providers emphasized relationship building in their counseling. 41 …”
Section: What Do We Know About How Contraceptive Counseling Is Performentioning
confidence: 97%
“…In interviews with physicians and nurses about the counselling strategies they used in conversations with patients around preventive sexual health consultations, Henderson, Raine, Schalet, Blum, and Harper (2011) found that these healthcare workers had evolved a combination of "parental" authority, empathic connection and innovative problem-solving, as a means of addressing the specific needs of their patient group. Other studies have also found that practitioners of embedded counselling have integrated existing counselling theories and approaches into idiosyncratic "situated working models" (see e.g.…”
Section: The Process and Outcome Of Training In Embedded Counselling mentioning
confidence: 99%